Pendampingan dan Pembekalan Katekis Pendamping Iman Sekolah Minggu di Semarang - Anselmus Joko Prayitno (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
One of the common vocations of Christians is to proclaim to all people of all ages. The age of the child is a golden age in development, it needs special attention in faith formation. Companions need to get enough training so that faith building in children will be right on target. Child assistance is usually carried out on Sundays so it is called Sunday school, Sunday School assistants are not professionals who get special education such as ECCE educators in schools. Many of these Sunday School faith companions are armed only to serve or guide this child's faith. This Community Service or PKM aims to equip Sunday School faith companions to be better in mentoring. With the right learning method or model, the faith materials given are in accordance with the child's reasoning and grasping power. The assistance was carried out by involving students to be directly involved in three rayon parishes in Semarang city and inviting all Semarang Rayon Sunday School Faith companions at Oak Tree Hotel on December 10, 2023, to share experiences and provide input to children's Faith Companions. As a result of this debriefing, Sunday School Faith Companions felt cared for and greatly helped in fostering faith in children.